Analisis Pengaruh Tingkat Kemiskinan Terhadap Indeks Pembangunan Manusia (IPM) Dengan Model Regresi Linier (Studi Kasus Di Kabupaten Bengkulu Utara Pada Tahun 2010-2021) - Martono Hadi Saputro (UNIVED Press, 2022)
This research is a study on economic problems that specifically examines the level of proverty and Human Development Index (HDI). This research aims to determine the effect of proverty spending on Human Development Index (HDI) in Bengkulu Utara Regency in 2010-2021. This research is a quatitative study with descriptive and associative research design, and object of research is the level of proverty and HDI. This study used time series data on level of proverty and The Human Development Index (HDI) from BPS Bengkulu Utara Regency in 2010-2021. The Techniques of Data Collection are documentation in the form of books, journals and reports. The analytical method used descriptive, simple correlation test, coefficient of determination test, regression test and partial hypothesis test (test-t) using SPSS software. The result of the coefficient of determination test show that the dependent variable can be explained by the independent variable by 57,2 %. The result of this variable, indicate by partially the proverty variable have a significant effect on HDI which is indicated by a probability value 0,004 smaller than alpha (0,005). The results of the partial analysis show that the level of proverty has a negative and significant effect on HDI.